Ozone Layer Depletion and Emerging Public Health Concerns - An Update on Epidemiological Perspective of the Ambivalent Effects of Ultraviolet Radiation Exposure - Umar, Sheikh Ahmad; Tasduq, Sheikh Abdullah (Frontiers in Oncology, 2022)
Solar ultraviolet (UV) radiation exposure is the primary etiological agent responsible for developing cutaneous malignancies. Avoiding excessive radiation exposure, especially by high-risk groups, is recommended to prevent UV-induced photo-pathologies. However, optimal sun exposure is essential for the healthy synthesis of about 90% of vitamin D levels in the body. Insufficient exposure to UV-B is linked to vitamin D deficiency in humans. Therefore, optimal sun exposure is necessary for maintaining a normal state of homeostasis in the skin. Humans worldwide face a major existential threat because of climate change which has already shown its effects in several ways. Over the last 4 to 5 decades, increased incidences in skin cancer cases have led international health organizations to develop strong sun protection measures. However, at the same time, a growing concern about vitamin D deficiency is creating a kind of exposure dilemma. Current knowledge of UV exposure to skin outweighs the adverse effects than the beneficial roles it offers to the body, necessitating a correct public health recommendation on optimal sun exposure. Following an appropriate recommendation on optimal sun exposure will lead to positive outcomes in protecting humans against the adverse effects of strict recommendations on sun protection measures. In this short review, we spotlight the ambivalent health effects of UV exposure and how ozone layer depletion has influenced these effects of UVR. Further, our aim remains to explore how to lead towards a balanced recommendation on sun protection measures to prevent the spurt of diseases due to inadequate exposure to UV-B.